2010
DOI: 10.1001/archsurg.2010.163
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Chemotherapy on Postoperative Complications After Mastectomy and Immediate Breast Reconstruction

Abstract: Although the highest rate of surgical site infections was in the adjuvant chemotherapy group, there were no differences between groups with respect to unplanned return to the operating room, expander loss, and donor-site complications. Neither the inclusion of chemotherapy nor the timing of its administration significantly affected the complication rates after mastectomy and immediate breast reconstruction in this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
58
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 123 publications
(63 citation statements)
references
References 20 publications
5
58
0
Order By: Relevance
“…However, a study by Decker et al [17] did reveal a trend toward increased wound complications in patients who received NAC and underwent mastectomies with immediate reconstruction, although it was not statistically significant (OR = 1.58; 95% CI = 0.98–2.58). For the 5 studies (n = 765 patients) that reported the influence of NAC on the occurrence of hematomas after surgery [9], [11], [21][23], the pooled result showed that there was no statistically significant difference in the incidence of hematomas between the 2 groups (OR = 1.35; 95% CI = 0.57–3.21; Fig. 3).…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…However, a study by Decker et al [17] did reveal a trend toward increased wound complications in patients who received NAC and underwent mastectomies with immediate reconstruction, although it was not statistically significant (OR = 1.58; 95% CI = 0.98–2.58). For the 5 studies (n = 765 patients) that reported the influence of NAC on the occurrence of hematomas after surgery [9], [11], [21][23], the pooled result showed that there was no statistically significant difference in the incidence of hematomas between the 2 groups (OR = 1.35; 95% CI = 0.57–3.21; Fig. 3).…”
Section: Resultsmentioning
confidence: 98%
“…Of the included reports, 6 studies [9], [18], [20], [21], [23], [28] described reconstruction outcomes including E/I loss during E/I reconstruction and total flap loss during autologous reconstruction. For E/I loss, 4 studies [9], [18], [20], [21] provided mixed results.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A few studies have attempted to determine the effect of chemotherapy on postoperative breast-implant infection 19,44,48,49. Peled et al analyzed 163 patients who underwent mastectomy and immediate reconstruction, including 66% implant-based and 33% autologous tissue-based reconstructions 48.…”
Section: Risk Factors For Implant Infectionmentioning
confidence: 99%
“…Peled et al analyzed 163 patients who underwent mastectomy and immediate reconstruction, including 66% implant-based and 33% autologous tissue-based reconstructions 48. The adjuvant-chemotherapy group had a significantly higher number of infections (44%) versus the neoadjuvant- and no-chemotherapy groups (23% and 25%, respectively).…”
Section: Risk Factors For Implant Infectionmentioning
confidence: 99%